M6a demethylase FTO regulates the oxidative stress, mitochondrial biogenesis of cardiomyocytes and PGC-1a stability in myocardial ischemia-reperfusion injury - Qiong Jiang; Xuehai Chen; Kezeng Gong; Zhe Xu; Lianglong Chen; Feilong Zhang (Redox Report)
Objective Myocardial ischemia-reperfusion injury (MIRI) is a highly complex disease with high morbidity and mortality. Studying the molecular mechanism of MIRI and discovering new targets are crucial for the future treatment of MIRI.Methods We constructed the MIRI rat model and hypoxia/reoxygenation (H/R) injury cardiomyocytes model. RT–PCR and Western blot were used to investigate the expression of the fat mass and obesity-associated (FTO) gene. Electrocardiogram, echocardiography, triphenyltetrazolium chloride (TTC) staining and hematoxylin-eosin (HE) staining were used to assess the model and the effect of FTO overexpression. The generation of reactive oxygen species (ROS) and the levels of superoxide dismutase (SOD2), mitochondrial transcription factor (TFAM) and cytochrome c oxidase I (COXI) were detected to assess the oxidative stress and mitochondrial biogenesis. RNA immunoprecipitation (RIP) and RNA pulldown assays were used to identify the interaction of FTO and PGC-1a. The m6A dot blot, methylated RNA immunoprecipitation PCR (MeRIP-PCR) and RNA stability analysis were used to analyze the regulation of methylation of PGC-1a by FTO.Results FTO was downregulated in MIRI rats and H/R induced cardiomyocytes. Overexpression of FTO inhibited ROS level and increased the expression of SOD2, TFAM and COXI in vitro and in vivo. In addition, PGC-1a was identified as a downstream target of FTO. FTO enhanced the stability of PGC-1a mRNA through removing the m6A modification.Conclusion Our study revealed the role of FTO regulates the oxidative stress and mitochondrial biogenesis via PGC-1a in MIRI, which may provide a new approach to mitigating MIRI.